SPHENOID WING DYSPLASIA: REPORT OF 3 CASES - Muhammad Umar Qayyum; Ehtesham, Ehtesham ul Haq; Syed Atif Mahmood Kazmi; Rubbab Zahra (Journal of Ayub Medical College Abbottabad, 2022)
Sphenoidal Dysplasia is the absence of complete or a part of sphenoid bone, most commonly the greater wing of sphenoid. It can occur as an isolated deformity or in Neurofibromatosis-1 (NF1). Features of NF1 include cafÃ© au lait spots, inguinal or axillary freckling, neurofibromas, optic gliomas, scoliosis and tibial deformity. Our study is retrospective case series of 3 cases of Sphenoid wing dysplasia. There was 1 case of isolated bone defect, 1 case of NF-1 and 1 case of operated Craniofacial Fibrous Dysplasia involving the sphenoid wing. There were 2 primary operated cases while 1 was operated secondarily. There was resolution of pulsatile exophthalmos in patient with sphenoid and temporal bone defect. Patient with facial deformity NF1 was debulked to the satisfaction of the patient, the patient however declined surgery to correct the sphenoid bone deformity. The 3rd patient was a re-do surgery patient in which the previous implant material was removed and the CSF rhinorrhoea, the patient did not consent to the correction of vertical orbital dystopia. Sphenoid wing dysplasia is a complex deformity requiring multi-speciality care and treatment planning. With meticulous planning and surgery, good results can be achieved as shown in our case series.